Costs and benefits of iodine supplementation for pregnant women in a mildly to moderately iodine-deficient population: a modelling analysis. Issue 9 (September 2015) - Monahan, Mark; Boelaert, Kristien; Jolly, Kate; Chan, Shiao; Barton, Pelham; Roberts, Tracy E
Summary: Background: Results from previous studies show that the cognitive ability of offspring might be irreversibly damaged as a result of their mother's mild iodine deficiency during pregnancy. A reduced intelligence quotient (IQ) score has broad economic and societal cost implications because intelligence affects wellbeing, income, and education outcomes. Although pregnancy and lactation lead to increased iodine needs, no UK recommendations for iodine supplementation have been issued to pregnant women. We aimed to investigate the cost-effectiveness of iodine supplementation versus no supplementation for pregnant women in a mildly to moderately iodine-deficient population for which a population-based iodine supplementation programme—for example, universal salt iodisation—did not exist. Methods: We systematically searched MEDLINE, Embase, EconLit, and NHS EED for economic studies that linked IQ and income published in all languages until Aug 21, 2014. We took clinical data relating to iodine deficiency in pregnant women and the effect on IQ in their children aged 8–9 years from primary research. A decision tree was developed to compare the treatment strategies of iodine supplementation in tablet form with no iodine supplementation for pregnant women in the UK. Analyses were done from a health service perspective (analysis 1; taking direct health service costs into account) and societal perspective (analysis 2; taking education costs and the value of an IQ point itself into account), and presented in terms of cost (in sterling, relevant to 2013) per IQ point gained in the offspring. We made data-supported assumptions to complete these analyses, but used a conservative approach that limited the benefits of iodine supplementation and overestimated its potential harms. Findings: Our systematic search identified 1361 published articles, of which eight were assessed to calculate the monetary value of an IQ point. A discounted lifetime value of an additional IQ point based on earnings was estimated to be £3297 (study estimates range from £1319 to £11 967) for the offspring cohort. Iodine supplementation was cost saving from both a health service perspective (saving £199 per pregnant woman [sensitivity analysis range –£42 to £229]) and societal perspective (saving £4476 per pregnant woman [sensitivity analysis range £540 to £4495]), with a net gain of 1·22 IQ points in each analysis. Base case results were robust to sensitivity analyses. Interpretation: Iodine supplementation for pregnant women in the UK is potentially cost saving. This finding also has implications for the 1·88 billion people in the 32 countries with iodine deficiency worldwide. Valuation of IQ points should consider non-earnings benefits—eg, health benefits associated with a higher IQ not germane to earnings. Funding: None.